Experimental shear testing of corrugated web girders with compression tubular flanges used in conventional buildings. (October 2022) - Deng, Hao; Shao, Yong-Bo; Hassanein, M.F.
Abstract: Steel corrugated web girders (SCWGs) have been extensively investigated and applied in bridges and buildings worldwide, due to their excellent out-of-plane stiffness of their webs and their high shear strengths. This paper proposes a new type of SCWGs based on previous literature, namely the girder including a hollow tubular compression flange, a corrugated web, and a flat lower flange. Small-scale specimens suiting building applications are designed and tested experimentally to examine their failure modes and bearing capacities under shear. Based on the test results, FE models are generated and validated accurately through the comparisons of the ultimate loads, load–deflection relationships and failure modes. Then, parametric studies are performed to increase the pool of available results of the current girders, from which the effects of tubular flange, web thickness, web height, web slenderness ratio and tube depth-to-width ratio are evaluated. It is found that the tube depth-to-width ratio has a great effect on the shear behaviour of SCWGs with the upper tubular flange. In the tests, the ratio of the shear force at the upper tubular flange to the shear of the corresponding cross-section is about 12%–18% for the flat folds, while the ratio is 9%–13% for the inclined folds. A minimum tube depth for the new kind of girder is suggested that yields higher strength compared with SCWGs with plate flange of the same area. Moreover, the results show that the post-buckling strength is improved by using the new kind of girders compared to conventional SCWGs with plate flanges. At the end, available shear design methods, originally suggested for SCWGs with plate flanges, are applied to the current girders to check their accuracy. The comparisons illustrate that these methods yield conservative predictions for SCWGs with tubular flanges for many cases but unconservative for few cases, highlighting the importance of proposing a new shear design model that takes into account the effect of the upper tubular flange in the near future. Highlights: Using ABAQUS, SCWGs with tubular flanges under shear are tested. Using ABAQUS, FE models of SCWGs with tubular flanges are developed. Main factors affecting the shear response of SCWGs with tubular flanges are discussed. The most accurate design model for SCWGs with tubular flanges is defined.